T is for Three-way - 10 Erotic Short Stories - L., Sara Agnès (Saga Egmont, 2023)
‘T is for Three-way - 10 Erotic Short Stories’ is a collection of erotica that invites a third person into the bedroom. Three-ways, threesomes, or a ménage à trois... three certainly isn’t a crowd in this collection. It might take two to tango, but it takes three to make these stories sexy and steamy.